Road Surface Damage Monitoring System using Machine Learning - Dr. Ansal K A; Er. Anu Raj; Mr. Novel IJK (Journal of Electronic Design Engineering, 2018)
A system to effectively monitor and evaluate the quality of the damaged road .This is achieved using an image classifier convolution neural network. This can be used for a wide variety of uses like safety warnings to the driver and the car computer, more accurate travel time estimations etc.